Know more of bipolar disorder as a form of disability - Abdul Khaiyom, Jamilah Hanum (2019)
Invited to be Interviewed by IIUM.FM for the Programme Empathy is Key: Creating Awareness of Disabilities with entitle discussion on "Know More of Bipolar Disorder as a Form of Disability. The content of discussion encompassed definition of bipolar, symptoms, causal factors, types of bipolar and its differences, bipolar as disability, treatment and intervention, and how general people may help.